Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1029/2021ef002289
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Big Data for Water Environment Monitoring: Current Status, Challenges, and Future Prospects

Abstract: Accurate water extraction and quantitative estimation of water quality are two key and challenging issues for remote sensing of water environment. Recent advances in remote sensing big data, cloud computing, and machine learning have promoted these two fields into a new era. This study reviews the operating framework and methods of remote sensing big data for water environment monitoring, with emphasis on water extraction and quantitative estimation of water quality. The following aspects were investigated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 150 publications
0
22
0
3
Order By: Relevance
“…Remote sensing satellites that are now publicly free available have both high time-frequency and high spatial resolution, i.e., Sentinel-2 A/B double satellites combination have a 5-day revisit period and a spatial resolution of 10m [2]. Satellite monitoring of water quality can achieve low-cost, high spatial and temporal resolution monitoring, but the larger error is its weakness [3]. The use of satellites for water quality monitoring has been widely used in oceans, inland lakes, and rivers [3], but few studies for monitoring wetland water quality have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote sensing satellites that are now publicly free available have both high time-frequency and high spatial resolution, i.e., Sentinel-2 A/B double satellites combination have a 5-day revisit period and a spatial resolution of 10m [2]. Satellite monitoring of water quality can achieve low-cost, high spatial and temporal resolution monitoring, but the larger error is its weakness [3]. The use of satellites for water quality monitoring has been widely used in oceans, inland lakes, and rivers [3], but few studies for monitoring wetland water quality have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite monitoring of water quality can achieve low-cost, high spatial and temporal resolution monitoring, but the larger error is its weakness [3]. The use of satellites for water quality monitoring has been widely used in oceans, inland lakes, and rivers [3], but few studies for monitoring wetland water quality have been reported. Therefore, the wetland remote sensing always focuses on ecosystem monitoring, soil matters and boundary changes [4]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…The advancement in micro/nanotechnology has significantly enriched the quality and reliability of miniaturized sensors needed across multiple sectors including health monitoring, , agriculture, aquaculture, environment monitoring, robotics, rehabilitation, , automation, space, , etc. Complemented by recent progress in flexible and printed electronics, these solutions continue to enrich the above areas and open new opportunities by allowing the detection of various chemical and biological analytes or parameters such as dopamine, glucose, tyrosine, and creatinine for human healthcare. , The rapidly aging society and new forms of lethal diseases have pushed healthcare systems to adopt innovative solutions such as digital healthcare, which have contributed immensely to the rising demand for portable and wearable chemical sensors and biosensors globally. Numerous selective and sensitive chemical sensors and biosensors have been reported in the literature using distinct working mechanisms and exploiting the optical, piezoelectric, electrochemical, and enzymatic properties of various sensing materials [e.g., metal–organic frameworks (MOFs), two-dimensional (2D) materials, conducting polymers, carbon nanotubes (CNTs)]. However, one of the long-standing problems with these sensors is the lack of a suitable source of power.…”
Section: Introductionmentioning
confidence: 99%
“…The advancement in micro/nanotechnology has significantly enriched the quality and reliability of miniaturized sensors needed across multiple sectors including health monitoring, 1 , 2 agriculture, 3 aquaculture, 4 environment monitoring, 5 robotics, 6 8 rehabilitation, 9 , 10 automation, 11 space, 12 , 13 etc. Complemented by recent progress in flexible and printed electronics, these solutions continue to enrich the above areas and open new opportunities by allowing the detection of various chemical and biological analytes or parameters such as dopamine, 14 glucose, 15 tyrosine, 16 and creatinine 17 for human healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Associando extensos bancos de dados e integrando-os, a ferramenta vem facilitando a produção e análise de informações, e, com isso, promovendo uma melhor gestão nas empresas e instituições (GOHIL et al, 2021;PONTES et al, 2021). Sua aplicação para a gestão e o planejamento público, de recursos hídricos e de outras infraestruturas de saneamento já vem sendo realizada (SUN; SCAN-LON, 2019) e expandida com o uso do geoprocessamento (ANA, 2019;CHEN et al, 2022;CRAVERO et al, 2018;WICKRAMASU-RIYA et al, 2013).…”
unclassified